The Relationship Between Transformational Resilience-Based Performance Model and Improvement in Work Productivity of Inpatient Nurses at Majalengka Regional General Hospital - Wahyuni, Restu Eka; Mulyati, Mulyati; Rohayani, Lilis (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Nurses are the frontline of hospital services and are required to remain effective despite work pressures, family dynamics, and social demands. The existing gap in productivity highlights the need to strengthen transformational resilience–based performance. Objective: This study aimed to analyze the relationship between transformational resilience–based performance and work productivity among inpatient nurses at Majalengka Regional General Hospital. Method: A quantitative study with a cross-sectional design was conducted, involving all inpatient nurses as the population (N = 259). A total of 157 nurses were selected using proportionate random sampling. Data analysis consisted of univariate (frequency distribution) and bivariate (2×2 chi-square test). Result and Discussion: Results showed that 62.4% of nurses had good resilience, and 76.4% demonstrated good productivity. There was a significant association between resilience and productivity (p = 0.010) with an odds ratio (OR) of 2.83 (95% CI: 1.33–6.03), indicating that nurses with good resilience were 2.8 times more likely to demonstrate good productivity. Conclusion: These findings emphasize the importance of evaluating and adjusting workloads to prevent excessive stress that could reduce resilience and nurse performance